Дослідження Торговицького середньовічного комплексу в 2008—2009 рр. - Козир, І.А.; Позивай, Т.Д. (Археологічні дослідження в Україні, 2010)
Results of excavations at the settlement and the burial ground of the Golden Horde period near Torhovytsya village in Kirovohrad Oblast are presented; where a large area of the eastern bath-house (hammam) was studied, and for the first time, a manufacturing complex with ceramic nozzles and tandirs was discovered.